Density functional theory computational study of ferroelectricity and piezoelectricity in BaTiO3/PbTiO3 (0 1 1) superlattices. (20th March 2018) - Lou, Yaoding; Deng, Junkai; Liu, Jefferson Zhe
Abstract: The structure, ferroelectricity (FE), and piezoelectricity of epitaxial BaTiO3 /PbTiO3 (BTO/PTO) (0 1 1) superlattices are studied using density functional theory calculations. Our results show that compressive strain arising from the SrTiO3 (0 1 1) substrate stabilizes the (BTO) m /(PTO) n (0 1 1) superlattices in orthorhombic phase with the FE polarization along [0 1 1] direction. Tuning the BTO contents significantly changes the structural, ferroelectric and piezoelectric properties. The FE polarization of superlattices significantly drops with increasing BTO contents, which can be attributed to depolarization of the PTO layers. The averaged c / a ratio of the whole superlattices exhibits anomalous non-monotonic relation with respect to BTO contents. Interestingly, our results predict the (0 1 1) superlattices can enhance the piezoelectric coefficient e 33 with a maximum value at ~67% BTO concentration. This result suggests a potential avenue to design high performance piezoelectric materials with less Pb contents. In-depth analysis reveals the B-site Ti cation as the origin for the enhanced e 33 value, which implies the potential of B-site cation engineering in perovskite heterostructure designs.